Memória temporal: é possível medir o tempo sem o espaço? - Gomes, Laís Farias (2021)
Besides intuitive, the concept of time is hard to define. Here we conceive time as a flow of events, which might relate to the duration of a certain stimulus or the sequencing of previously presented items; in other words: a perception of time intervals or the ordering of stimuli. Studies with rodents might provide interpretation to some phenomena, considering the analogy with humans, the knowledge about their biology and the closer phylogenetic relation with our species, apart from non-human primates. Protocols based on rodents aim to establish behavioral evidence of a memory trace, and they can have different configurations. In this work, we divided the temporal memory protocols in categories and analyzed the advantages and disadvantages of odor tasks and object recogntion tasks, in order to discuss the methodological and physiological basis of these tasks. Different protocols are used to assess temporal memory. The use of spontaneous object exploration in animal models has many advantages, and the protocol developed by Mitchell and Laiacona (1998) has become commonplace. Here we investigated a possible “spatial bias” within this experimental design. For this, Wistar rats underwent novel tasks, developed by our Lab team, similar to the original protocol, but adding object displacement during the experimental session. In the sample and test sessions of the TOM-R task, objects always occupied different locations in the open field. In the sample sessions of the TOM-K task, objects occupied different locations in the open field, but in 28 the test session of this task, the objects occupied previously known locations. In addition, we provided landmarks for a group of rats tested in those protocols, and another group of rats were tested in the absence of landmarks. The results from the TOM-R task showed that the the absence of a spatial reference impairs the recency discrimination. On the other hand, the rats exhibited temporal memory in the TOM-K task. The animals were also tested in those tasks in the presence and absence of landmarks, but the same pattern of results were acquired. Based on these findings, we discussed the possibility that the memory trace for “space” is more robust than the the memory trace for “time”. We also looked at these data considering the rat´s biology. An alternative explanation is that time processing might be intrinsically linked to space processing, which is consistent with the findings from the neurobiology of temporal memory. This study adds to the investigation of the element “time”, an essential factor for elucidating one of the most intriguing psychological process: episodic memory.